Canadian Shield Volcanic Belts with Emphasis on the Abitibi Volcanic Pile - Gélinas, L.; Brooks, C.; Barager, R. (Geoscience Canada, 1974)
Summary The Quebec part of the Abitibi volcanic belt is the subject of an intensive research project oriented towards providing detailed petrological and geochemical data integrated with stratigraphy and tectonics. In establishing the changing composition of the volcanic pile in the region north and south of Rouyn (from monotonous tholeiite basalt in the lower sections to intermingled calc-alkaline and tholeiitic series in the higher sections) such diverse subjects as the role of immiscibility in the formation of variolites, and the nature of quench-texture in Archean tholeiites have been investigated. A conference series designed to provide a means of exchange of information between project personnel and researchers investigating related topics elsewhere in Canada was convened. The feedback obtained during the conference series resulted in new directions being initiated within the confines of the project, and a complete traverse of the Abitibi volcanic pile from south of Rouyn to Matagami is planned.